Learning from product labels and label changes: how to build pharmacogenomics into drug-development programs. (December 2010) - Surh, Linda C; Pacanowski, Michael A; Haga, Susanne B; Hobbs, Stuart; Lesko, Lawrence J; Gottlieb, Scott; Papaluca-Amati, Marisa; Patterson, Scott D; Hughes, Arlene R; Kim, Myong-Jin; Close, Sandra L; Mosteller, Michael; et al.
The 2010 US FDA–Drug Industry Association (DIA) Pharmacogenomics (PGx) Workshop follows a series that began in 2002 bringing together multidisciplinary experts spanning regulatory authorities, medical research, healthcare and industry. This report summarizes the 'Building PGx into Labels' sessions from the workshop, which discussed the critical elements in developing PGx outcomes leading to product labels that inform efficacy and/or safety. Examples were drawn from US prescribing information, which integrated PGx knowledge into medical decisions (e.g., panitumumab, warfarin and clopidogrel). Attendees indicated the need for broader dialog and for guidelines on evidentiary considerations for PGx to be included into product labels. Also discussed was the understanding of appropriate PGx placement on labels; how to encourage adoption by medical communities of label recommendations on PGx tests; and, given the global nature of drug development, worldwide considerations including European Summary of Product Characteristics.